2-Phenylpyridine Derivatives: Synthesis and Insecticidal Activity against Mythimna separata, Aphis craccivora, and Tetranychus cinnabarinus - Wenliang Zhang; Jingjing Chen; Xiaohua Du (Molecules, 2023)
The increase in the insecticide resistance of pests, such as Mythimna separata, Aphis craccivora Koch, and Tetranychus cinnabarinus, necessitates the development of new heterocyclic compounds with high insecticidal activity. A series of novel 2-phenylpyridine derivatives containing N-phenylbenzamide moieties were designed and synthesised with Suzuki–Miyaura cross-coupling, nucleophilic substitution, and amidation reactions. The reaction conditions in each step are mild, and the product is easy to separate (yield is about 85%). The structures of the compounds were characterised using 1H and 13C NMR spectroscopy and HRMS. Moreover, the insecticidal activity of the compounds was analysed using the leaf dipping method. The compounds 5a, 5d, 5g, 5h, and 5k at 500 mg/L exhibited 100% inhibition against Mythimna separata. Therefore, the 2-phenylpyridine moieties have the potential to lead to the discovery of novel and effective insecticides.